Persepsi Pemuda-Pemudi terhadap Strategi Pelayanan Pendeta dalam Pembentukan Karakter di GKPI Silaban Margu Doloksanggul - Kevin Leonardo Tarihoran; Nurelni Limbong; Megawati Manullang; Haposan Silalahi; Hanna Dewi Aritonang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study is a qualitative study with data collection methods through tests and interviews. Respondents consisted of young men and women, elders, and parents. The purpose of the study was to determine the perceptions of young men and women towards the role and strategy of pastoral service in character building at GKPI Silaban Margu Resort Doloksanggul I, Humbang Hasundutan Regency. The character that is built is based on the character of Christ, including attitudes such as honesty, responsibility, discipline, respect, and values ​​such as self-confidence, patience, caution, and trustworthiness. Pastors play an important role in guiding young men and women through service and planning activities that support character building. In addition, pastors are expected to be able to be present and actively involved among young men and women, provide positive influences, and encourage character growth that is in accordance with Christian values ​​to support church growth.